Contribution of regenerated forest in conservation of bats in Peninsular Malaysia - RMD, Mohd-Hanif; MT, Nur-Aida; AR, Zahirunisa; AR, Mohd-Ridwan; MT, Abdullah (Forest Research Institute Malaysia, 2015)
Surveys of bats were conducted at six regenerated forest sampling sites, namely, Sungai Dusun Forest Reserve (FR), Fraser Hill FR, Lata Bujang FR, Tasek Bera FR, Endau–Kluang FR and Endau–Kota Tinggi FR. A total of 289 individuals representing 35 species of bats were recorded. Endau–Kota Tinggi FR was the most diverse (Fisher’s α = 9.95) while Endau–Kluang FR, the least diverse (Fisher’s α = 3.17). Six species of bats, namely, Dyacopterus spadiceus, Nycteris tragata, Rhinolophus sedulus, Kerivoula intermedia, K. pellucida and Myotis ridleyi are listed as near threatened. Two species of bats, Hipposideros ridleyi and Arielulus societatis, are listed as vulnerable and facing high risk of extinction in the wild. The diversity of chiropterans in generated forest was high and was underestimated because of lack of information on those high flier species in and above canopy levels.